The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s00330-011-2103-9
|View full text |Cite
|
Sign up to set email alerts
|

Sonoelastographic lesion stiffness: preoperative predictor of the presence of an invasive focus in nonpalpable DCIS diagnosed at US-guided needle biopsy

Abstract: Sonoelastographic lesion stiffness is an independent preoperative predictor of invasion in some patients with nonpalpable DCIS at US-guided needle biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 31 publications
(63 reference statements)
4
10
1
Order By: Relevance
“…The previous study reported that the mean elasticity score of intraductal papillomas was higher than that of benign proliferative lesions (2.9±1.0 vs. 1.7±0.9, respectively) (P<0.01) [2]. However, contrary to their results showing no difference in elasticity scores between DCIS and IDC, we found that the mean elasticity score of IDC was higher than that of DCIS (3.26±0.09 vs. 2.54±0.11, respectively) (P<0.001), which is similar to the results of another study [17].…”
Section: Discussioncontrasting
confidence: 76%
“…The previous study reported that the mean elasticity score of intraductal papillomas was higher than that of benign proliferative lesions (2.9±1.0 vs. 1.7±0.9, respectively) (P<0.01) [2]. However, contrary to their results showing no difference in elasticity scores between DCIS and IDC, we found that the mean elasticity score of IDC was higher than that of DCIS (3.26±0.09 vs. 2.54±0.11, respectively) (P<0.001), which is similar to the results of another study [17].…”
Section: Discussioncontrasting
confidence: 76%
“…Because invasive cancers tend to be stiffer than DCIS lesions, homogeneous stiffness on strain elastography predicted an increased likelihood of an upgrade to invasive carcinoma at excision after a core biopsy showing DCIS in one series [25]. We confirmed that DCIS is softer, on average, than invasive breast cancer, with a median Emax of 126 kPa for DCIS versus 180 kPa for invasive cancers (p = 0.002) in our series.…”
Section: Berg Et Alsupporting
confidence: 71%
“…This result can be explained by the fact that DCIS tends to show less suspicious features than invasive cancers on B-mode ultrasonography [22], tending to be classified as BI-RADS category 3. Furthermore, as DCIS is softer than invasive cancers [16], it is more difficult to distinguish DCIS from benign lesions than to distinguish invasive cancers from benign lesions on US elastography. In a previous study using the same elasticity score as our study, although the mean elasticity score of DCIS was higher than that of benign disease (2.54±0.11 vs. 1.78±0.81; P<0.001), the mean elasticity score of DCIS was lower than that of invasive ductal carcinomas (2.54±0.11 vs. 3.26±0.09; P<0.001) [14].…”
Section: Discussionmentioning
confidence: 99%